Executive function in the first three years of life: Precursors, predictors and patterns - Hendry, Alexandra; Jones, Emily J.H.; Charman, Tony (Developmental review, 2016)
•Cross-discipline research relating to emergent executive function (EF) is reviewed.•Individual differences in infancy affect later EF.•Attention control, self-regulation and processing speed are foundational to EF.•By age 3, infants can demonstrate impulse control and cognitive flexibility. Executive function (EF) underpins the ability to set goals and work towards those goals by co-ordinating thought and action. Its emergence during the first 3 years of life is under-studied, largely due to the limitations that early social, motor and language skills place on performance on traditional EF tasks. Nevertheless, across the fields of cognitive psychology, neuroscience, social development and temperament research, evidence is amassing of meaningful precursors and predictors of EF. This review draws together the evidence, highlighting methodological considerations and areas of theoretical debate, and identifies 4 domains critical to the development of EF: control of attention, self-regulation, processing speed and cognitive flexibility. Individual differences within these domains have clinical significance both in terms of the identification of risk markers for later executive dysfunction and for the target or delivery of early intervention to ameliorate this risk. By the end of the third year, typically-developing infants are able to selectively employ impulse control and cognitive flexibility to achieve goal-directed responses to novel situations.